The effects of aviation-style non-technical skills training on technical performance and outcome in the operating theatre. - McCulloch, P; Mishra, A; Handa, A; Dale, T; Hirst, G; Catchpole, K (2009)
Unintended harm to patients in operating theatres is common. Correlations have been demonstrated between teamwork skills and error rates in theatres. This was a single-institution uncontrolled before-after study of the effects of "non-technical" skills training on attitudes, teamwork, technical performance and clinical outcome in laparoscopic cholecystectomy (LC) and carotid endarterectomy (CEA) operations. The setting was the theatre suite of a UK teaching hospital. Attitudes were measured using the Safety Attitudes Questionnaire (SAQ). Teamwork was scored using the Oxford Non-Technical Skills (NOTECHS) method. Operative technical errors (OTEs), non-operative procedural errors (NOPEs), complications, operating time and length of hospital stay (LOS) were recorded. A 9 h classroom non-technical skills course based on aviation "Crew Resource Management" (CRM) was offered to all staff, followed by 3 months of twice-weekly coaching from CRM experts. Forty-eight procedures (26 LC and 22 CEA) were studied before intervention, and 55 (32 and 23) afterwards. Non-technical skills and attitudes improved after training (NOTECHS increase 37.0 to 38.7, t = -2.35, p = 0.021, SAQ teamwork climate increase 64.1 to 69.2, t = -2.95, p = 0.007). OTEs declined from 1.73 to 0.98 (u = 1071, p = 0.009), and NOPEs from 8.48 to 5.16 per operation (t = 4.383, p<0.001). These effects were stronger in the LC group than in CEA procedures. The operating time was unchanged, and a non-significant reduction in LOS was observed. Non-technical skills training improved technical performance in theatre, but the effects varied between teams. Considerable cultural resistance to adoption was encountered, particularly among medical staff. Debriefing and challenging authority seemed more difficult to introduce than other parts of the training. Further studies are needed to define the optimal training package, explain variable responses and confirm clinical benefit.